Nitrite effect on nitrous oxide emission from denitrifying activated sludge - Alinsafi, Asma; Adouani, Nouceiba; Béline, Fabrice; Lendormi, Thomas; Limousy, Lionel; Sire, Olivier (Process biochemistry (1991), 2008)
Laboratory-scale experiments were conducted to examine the N 2O emission during the denitrification process. For each of the 6 runs carried out, synthetic effluent was fed in a 10 l batch mixed liquor to investigate the effect of nitrite on N 2O emission and Helium was continuously bubbled through the reactor at constant rate (0.12 l/min) to favour N 2O transfer and detection. An increasing COD/NO 3 −-N influent ratio from 3 to 7 was firstly applied (runs 1–3). Secondly, NO 2 − pulse additions were performed during run 4 and 5 (10 and 20 mg N/l, respectively). Finally, the reactor was fed with influent containing both NO 2 − and NO 3 −. We showed that N 2O emission was detected shortly after NO 2 − accumulation, few minutes after the substrate feeding. The highest emission occurred at the lower COD/NO 3 −-N ratio (=3) and at the higher NO 2 − addition (20 mg N/l). In addition, the higher nitrogen conversion to N 2O gas (14.4%) was obtained with an influent containing initially both NO 2 − and NO 3 −. Our results suggest a direct effect of the NO 2 − concentration on the N 2O emission. We have also confirmed the inhibitory effect of NO 2 − concentration on N 2O reduction.